Legal nature of mediation in the conditions of armed conflict - Sliusarenko, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Mediation in the realities of the modern world is one of the most common methods of peaceful resolution of armed conflicts, mainly due to its flexible procedure, which allows the parties to voluntarily decide on their participation in mediation, to freely choose a mediator, and to accept or reject the terms of conflict resolution established during the mediation procedures.M e t h o d s . Dialectical, historical, comparative legal methods were used during the study of the reasoning of mediator scientists regarding the expediency of using the mediation procedure during the settlement of conflict situations; systemic-structural, formal-logical methods – to determine provisions that should be taken into account in the process of using mediation in conditions of armed conflict; methods of analysis, generalization and synthesis – for the development of author's proposals regarding the expediency of using the mediation procedure and the direct involvement of mediators in working with military personnel, civilians and during negotiation processes.R e s u l t s . The study of different views of scientists on the role of a mediator – as a mediator directly during international political negotiations and peaceful settlements in the conditions of an armed conflict – is summarized and systematized. The main factors affecting the nature, process and directly the result of mediation in conditions of armed conflict are outlined. The role of a mediator during work on reconciliation with the civilian population and military personnel in conditions of armed conflict, as well as a negotiator during the negotiation process between warring parties is determined, and the mediation procedure is considered as an international instrument of reconciliation. The areas in which it is appropriate to use mediation in practice during various phases of military conflicts and for the sake of building a world culture of reconciliation have been developed and described.C o n c l u s i o n s . The results of this study develop a new approach to the application of the mediation procedure (mediation) during the resolution of armed conflicts, characterize the main subjects of mediation – the parties to the conflict and the mediator, and analyze their decisions regarding the use of the mediation procedure. The study provides a better understanding of the complexity of mediation in an armed conflict. The article proposes to consider mediation as a rapidly growing field and practice of intercultural and international mediation and reconciliation.
Keywords: armed conflict, mediation, mediation procedure, mediation, parties, mediator, reconciliation